Insurgent truth Chelsea Manning and the politics of outsider truth-telling - Maxwell, Lida (Oxford University Press, 2019)
"This book is about Chelsea Manning's leaking of government documents. Manning told the truth about war and a social order sustained by it. Her truth-telling also revealed the complicity of public and private in casting her - a non-gender-conforming individual - as an improper truth-teller. And Manning's truth-telling unsettled hierarchies of truth-telling that prop up a discriminatory and often oppressive social order. I read Manning not as an isolated political actor, but instead as an outsider truth-teller within a cohort of outsider truth-tellers (such as Virginia Woolf, Bayard Rustin, Audre Lorde), whose practices are distinct yet connected, and whose significance becomes more apparent when read in conjunction with each other"--